Prevalence of multi-ingredient pre-workout ergogenic and protein supplement use and effect on kidney function among university students and athletes in Benghazi, Libya - H. Ibrahim, Naser; Alhassi, Amal; Mohammed, Marwa; Othman, Afrah; Aldarrat , Khiriya (Libyan Journal of Public Health Practices, 2025)
The use of multi-ingredient pre-workout supplements (MIPS) is becoming increasingly common among university students and athletes, driven by the perceived benefits of increased energy, endurance, and muscle performance. However, the overuse of protein, particularly in this context, raises concerns regarding renal health. Few studies have addressed this issue in North African populations. A cross-sectional study was conducted among 244 students and athletes in Benghazi (56.6% males, 43.4% females). Data were collected via online questionnaire and analyzed using SPSS v22. A subgroup (n=30) underwent renal function testing, including serum urea, creatinine, uric acid, and electrolytes. Chi-square tests and Pearson correlations were used (P < 0.05). Male participants reported significantly higher supplement use (71.02%) than females (41.51%, P < 0.001). Nevertheless, (37.68%) of males compared to females (42.45%) reported that they would consume ergogenic supplements if they were encouraged by their coaches. Protein supplement use was positively associated with income (r = 0.229, P = 0.001). As for the detrimental effects on kidney function, renal testing indicated elevated urea and uric acid among MIPS users, suggesting potential kidney strain. MIPS are widely used among students and athletes in Benghazi, with notable gender differences in usage and perception. MIPS potential detrimental effects on kidney function raise concerns about safety and health risks among younger users. A deeper understanding of these supplements' risks and benefits is crucial for informed decision-making. This study is among the first in Libya to examine the physiological effects of MIPS use, offering critical insight into an under-researched population